Importance of RNF213 polymorphism on clinical features and long-term outcome in moyamoya disease - Kim, Eun-Hee; Yum, Mi-Sun; Ra, Young-Shin; Park, Jun Bum; Ahn, Jae Sung; Kim, Gu-Hwan; Goo, Hyun Woo; Ko, Tae-Sung; Yoo, Han-Wook (Journal of neurosurgery, 2016)
OBJECT Moyamoya disease (MMD) is an idiopathic cerebrovascular occlusive disorder prevalent in East Asia. In the pathogenesis of MMD, the important role of genetic factors is being elucidated, and RNF213 has recently been identified as a susceptibility gene for MMD. The aim of this retrospective study was to investigate the RNF213 genotype in patients with MMD and to determine their genotype-phenotype associations. METHODS The study involved 165 Korean MMD patients from 155 unrelated families who were diagnosed with MMD at a single center from 1995 to 2013. Their demographic, radiological, and clinical findings were evaluated. Direct sequencing of the major RNF213 single nucleotide polymorphisms was performed. The association of the common RNF213 variant with MMD risk was evaluated using historical controls for comparison. Correlations between RNF213 genotype and phenotype were statistically analyzed. RESULTS The c.14429G>A (p.R4810K) variant was identified in 125 (75.8%) of 165 MMD patients. Most patients (112) were heterozygous, and 13 patients had 2 copies of the c.14429G>A variant. A novel heterozygous variant, c.12086A>G (p.Q4029R), was found in 1 additional patient. The minor allele frequency of the c.14429G>A variant was significantly higher in the MMD group (138 [41.8%] of 330 patients) than in the control group (8 [1.36%] of 588 subjects; p < 0.001). The c.14429G>A (p.R4810K) variant significantly increased the risk of MMD in Korean patients, with an OR of 52.11 (p < 0.001) compared with controls. Moreover, c.14429G>A (p.R4810K) genotypes occurred more frequently in patients with a family history of MMD. The homozygous variant was highly associated with early-onset MMD (age at onset < 5 years), cerebral infarction at diagnosis, and cognitive impairment in long-term outcome. CONCLUSIONS The findings indicate that the c.14429G>A (p.R4810K) allele of RNF213 is strongly associated with Korean patients with MMD. The homozygous c.14429G>A (p.R4810K) variant is particularly related to early-onset MMD, severe symptomatic manifestations at diagnosis, and poor prognosis. This genotypic variant may be a useful biomarker for early-onset MMD or unstable MMD with cerebral infarction, which requires early diagnosis and revascularization treatment.